Uterine contractility changes in a perfused swine uterus model induced by local anesthetics procaine, lidocaine, and ropivacaine - Weinschenk, Fabian; Weinschenk, Stefan (PLOS ONE, 2018)
BACKGROUND: Local anesthetics (LAs) are increasingly used as therapeutics due to their multiple molecular effects. They may be potential agents also in gynecology and reproductive medicine. The objective of this study was to investigate the contractility response of the perfused swine uterus to different concentrations of the LAs procaine, lidocaine, and ropivacaine. - METHODS AND FINDINGS: In an extracorporeal perfusion model with fresh swine uteri, effects of administered boli of these three LAs in concentrations of 0.1 mg/mL, 0.5 mg/mL and 1.0 mg/mL on uterine contractility and peristalsis were assessed using an intrauterine double-chip micro-catheter. A dose-dependent increase in intrauterine pressure (IUP) in the isthmus and corpus uteri was observed after the administration of the ester-LA procaine 0.1, 0.5, and 1.0%, which was not seen with lower concentrations, or buffer solution. An increase-decrease curve was found after increasing concentrations of the amide-LA lidocaine and ropivacaine, with an IUP plateau with 0.1 and 0.5%, and a decrease with 1% (p<0.01). All reactions were seen in both the isthmus and corpus uteri. The difference of the contractility pattern between ester- and amide-LA at 1% concentration was significant. - CONCLUSION: LAs dose-dependently modulate contractility in non-pregnant swine uteri. The amid-LAs lidocaine and ropivacaine reduce contractility in higher concentrations and may be used as therapeutics in disorders with increased uterine contractility, as dysmenorrhoea, endometriosis, and infertility. The multiple molecular effects of LAs may explain these effects. This in-vitro pilot study in vitro provides initial data for designing further studies to transfer the results onto humans.